Adapting strategies to promote implementation reach and equity (ASPIRE) in school mental health services. Issue 12 (8th April 2021) - Gaias, Larissa M.; Arnold, Kimberly T.; Liu, Freda F.; Pullmann, Michael D.; Duong, Mylien T.; Lyon, Aaron R.
Abstract: Despite evidence that school mental health can enhance access to care for students from marginalized racial/ethnic groups, disparities remain in the appropriateness, quality, effectiveness, and outcomes of school mental health services. Implementation strategies hold some promise for addressing the disparities that emerge as result of inequitable implementation of mental health services. However, without explicitly examining implementation strategies through an equity lens, it is unclear the extent to which they will promote equitable implementation or student outcomes. Thus, the goal of the current paper is to describe the Adapting Strategies to Promote Implementation Reach and Equity framework, a generalizable process for adapting implementation strategies to explicitly center the goal of reducing disparities in implementation and service recipient outcomes. We outline a three‐step process for incorporating an equity lens into implementation strategies and provide examples of how this framework can be applied to implementation strategies in school mental health. We also discuss examples of projects where implementation strategies were intentionally paired with school mental health programs to enhance racial equity. Implications and recommendations for school mental health and implementation research and practice are discussed.